Religion and state in Tanzania revisited: reflections from 50 years of independence - Ndaluka, Thomas Joseph; Wijsen, Frans; Kipacha, Ahmad; Kilaini, Methodius; Lyimo, Francis F.; Sambaiga, Richard (Interreligious studies, 2014)
Preface / Hamza Njoziix. - Chapter One: Introduction Thomas Ndaluka, Bertram Mapunda ChapterTwo: An Overview of the Historiography of Religion and State in Post-Colonial Tanzania, 1960s to the Present / Oswald Masebo. - Chapter Three: Religion and the State in Tanzania: a Historical Perspective with Reference to the White Fathers in Buhaand Unyamwezi, 1878-1990s / Salvatory Nyanto. - Chapter Four: Ecumenism, Dialogue and Inculturation in the Church of Westernand North-western Tanzania: Responses to the Second Vatican Council / SalvatoryNyanto and M.Kilaini. - Chapter Five: "Things are Getting out of Control": an Analysis of Muslim Revivalism Discourses inTanzania / Thomas Ndaluka, Salvatory Nyanto, Frans Wijsen. - Chapter Six: "We are Ill-treated": a Critical Discourse Analysis of Muslims' Social Differentiation Claims in Tanzania / Thomas Ndaluka. - Chapter Seven: Religious Communities and Their Participationin Development Processesin Tanzania / Francis Lyimo. - Chapter Eight: Religious Teachings and Development Concepts in Tanzania: Insights from Tangaand Arumeru / Ahmad Kipacha, Justina Dugbazah, Simeon Mesaki. - Chapter Nine: Religion, State and Adolescent Sexuality in Tanzania: an Anthropological Perspective / Richard Sambaiga. - Chapter Ten: Relationship between the State and African Religion in Tanzania / Evaristi Magotti. - Chapter Eleven: Globalisation and Social Change: A Reflection of Religion and Religiosity in Tanzania / Huruma Sigalla. - Chapter Twelve: Secularization and the Rise of Religious Fundamentalismin Tanzania / Sam Maghimbi. - Chapter Thirteen: "Keep the Conversation Going": Regulating Islami Revivalismin Tanzania / Frans Wijsen. - Society and Religion Research Centre (SORRECE), University of DaresS alaam